2022
DOI: 10.2174/1568009622666220301145013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Expression Profile and Prognostic Significance of the IGF2BP Family in Lung Adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD),the most common type of lung cancer associated with poor prognosis, has become a major health problem for human health. IGF2BPs are types of N6-methyladenosine reader proteins, comprising IGF2BP1, IGF2BP2, and IGF2BP3, that promote LUAD progression. However, the expression profiles and prognostic value of IGF2BPs in LUAD remain unclear. Objective: To analyze the expression profiles and prognostic significance of the IGF2BP family in lung adenocarcinoma. Methods: In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…IGF2BP regulatory proteins are RBPs that modulate cellular functions including cell proliferation, differentiation, migration, and cancer invasion (Ramesh‐Kumar & Guil, 2022). We have previously shown that IGF2BP2 protein expression plays a significant role in lung adenocarcinoma development and progression (Zhou et al, 2022). IGF2BP family proteins are N 6 ‐methyladenosine (m 6 A) regulators.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP regulatory proteins are RBPs that modulate cellular functions including cell proliferation, differentiation, migration, and cancer invasion (Ramesh‐Kumar & Guil, 2022). We have previously shown that IGF2BP2 protein expression plays a significant role in lung adenocarcinoma development and progression (Zhou et al, 2022). IGF2BP family proteins are N 6 ‐methyladenosine (m 6 A) regulators.…”
Section: Discussionmentioning
confidence: 99%
“…YTHDF1, with METTL14, promoted double-stranded break (DSB) DNA damage repair and YTHDF1 knockdown increased sensitivity to adriamycin, cisplatin, and olaparib in MDA-MB-231 cells (Sun et al 2022). FOXM1, which promotes BC metastasis, is a YTHDF1 target and binding of YTHDF1 to FOXM1 mRNA for accelerated translation of FOXM1 in MCF-7 cells (Chen et al 2022). Binding of YTHDF1 to PKM2 mRNA stabilized the transcript to increase translation efficiency, which increased glycolytic activity in MBA-MD-231 and MCF-7 cells (Yao et al 2022).…”
Section: M6a Readers In Breast Cancermentioning
confidence: 99%
“…For example, HNRNPC expression promoted cell proliferation by inducing MAPK signaling in MDA-MB-231 and MCF-7 cells (Lv et al 2021). HNRNPK promotes invasion and metastasis in MDA-MB-231 and MDA-MB-468 cells by interacting with PROX1 and stimulating the WNT pathway (Zhu et al 2022).…”
Section: M6a Readers In Breast Cancermentioning
confidence: 99%
“…Simultaneously, FTO inhibition enhances the response to anti-PD-1 therapy in mice ( 130 ). The IGF2BP family, a regulatory subunit of m6A readers, is positively correlated with PD-1 expression, demonstrating that m6A modification regulated by the IGF2BP family may have potential benefits for patients with lung adenocarcinoma treated with ICIs ( 133 ). In recent years, integrative and comprehensive genomic and molecular analyses have been established to explore potential prognostic targets predicting the response of patients with pancreatic cancer to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%